A CRIMINOLOGICAL REVIEW OF THEFT COMMITTED BY JUVENILES IN THE JURISDICTION OF THE TAMPAN SECTOR POLICE - s, Zulkarnain; Yanti, Evi (Proceeding International Conference on Social Sciences, 2026)
This study aims to examine the factors contributing to theft committed by juveniles and to analyze the efforts undertaken by the Tampan Sector Police (Polsek Tampan) in addressing juvenile theft within its jurisdiction. The research focuses on understanding juvenile delinquency from a criminological perspective and evaluating law enforcement responses that emphasize child protection and restorative justice.This research employs an observational and descriptive methodology using a survey approach. Data were collected through interviews with law enforcement officers of the Tampan Police Station and juveniles involved in theft cases, supported by secondary and tertiary legal materials. The study analyzes the data qualitatively to identify causal factors and law enforcement strategies in handling juvenile theft.The findings indicate that juvenile theft in the jurisdiction of Polsek Tampan is influenced by multiple interrelated factors, including family conditions, environmental influences, economic pressures, educational limitations, and the rapid development of information and communication technology. Furthermore, the study reveals that Polsek Tampan implements integrated countermeasures through pre-emptive, preventive, and repressive approaches. Pre-emptive efforts focus on community development and legal awareness, preventive measures emphasize police presence and situational crime prevention, while repressive actions prioritize restorative justice through diversion mechanisms in accordance with the Juvenile Criminal Justice System.The study concludes that addressing juvenile theft requires a comprehensive approach that combines law enforcement with social intervention and community involvement. Strengthening inter-agency cooperation and enhancing legal awareness among youth are essential to preventing juvenile involvement in criminal activities and ensuring the protection of children’s rights within the criminal justice system.